The BASES expert statement on mental health literacy in elite sport. Produced on behalf of the British Association of Sport and Exercise Sciences - Gorczynski, P.; Gibson, K.; Thelwell, R.; Papathomas, A.; Harwood, C.; Kinnafick, F. (The Sport and Exercise Scientist, 2018)
Research demonstrates that elite athletes are not immune to poor mental health (Gorczynski et al., 2017; Rice et al., 2016), which can adversely affect their overall health and performance. Here, elite sport is defined on a continuum from semi-elite (e.g. high-performance youth development programmes) to world-class elite (e.g. global competitions) (Swann et al., 2015). There are many reasons why elite athletes may experience poor mental health. Training and performance demands can place considerable psychological stress on elite athletes who also face public and media scrutiny, financial concerns, sudden and prolonged injuries, and retirement, especially when unexpected. Despite these challenges, few elite athletes seek professional help for their mental health.